SPECIAL CHILDREN’S FESTIVAL: IMPLEMENTING BEHAVIORAL THERAPY THROUGH INTRODUCING JAPANESE CULTURE FOR CHILDREN WITH SPECIAL NEEDS - Algristian, Hafid; Khoirul Fitriyah, Fifi; Khamida, Khamida; Zuhdi, Ubaidillah; March Nur Huda, Salsadilla; Bagus Heryarudra Sundoro, Aditya; Khairul Bariyah, Khadijah (Community Service Journal of Indonesia, 2025)
Children with Special Needs (CSN) in Surabaya still face limitations in conventional therapy services that tend to focus on symptom management, necessitating a more inclusive and enjoyable alternative approach. The Special Children Festival program presents an innovation through implementing Japanese culture-based behavioral therapy to improve children's emotional regulation, focus, and fine motor skills. The novelty of this activity lies in integrating cultural elements into behavioral therapy and strengthening collaboration between hospitals, universities, and the community. The activity was held on June 28, 2025, at Campus B UNUSA, involving 14 CSN and their parents, three therapists from RSI Jemursari Surabaya, one Japan Corner facilitator, and six UNUSA Medical Faculty students. The implementation method included participatory observation and feedback analysis. The intervention consisted of onigiri-making and Japanese calligraphy (shodo) sessions, preceded by education for parents about culture-based behavioral therapy. Evaluation was conducted by assessing children’s engagement, responses during the activities, and parents’ perceptions of the program’s usefulness. This activity increased CSN participation and had a positive impact on focus, emotional regulation, and fine motor skills. Promotion strategies through parent communities and digital media proved effective in participant recruitment. Service standardization through training and certification of support staff enhanced service quality and sustainability, making this program a replicable model for culture-based behavioral therapy for CSN.